Crystal structure of the predicted phospholipase LYPLAL1 reveals unexpected functional plasticity despite close relationship to acyl protein thioesterases - Marco Bürger (Journal of Lipid Research, 2012)
Sequence homology indicates the existence of three human cytosolic acyl protein thioesterases, including APT1 that is known to depalmitoylate H- and N-Ras. One of them is the lysophospholipase-like 1 (LYPLAL1) protein that on the one hand is predicted to be closely related to APT1 but on the other hand might also function as a potential triacylglycerol lipase involved in obesity. However, its role remained unclear. The 1.7 Å crystal structure of LYPLAL1 reveals a fold very similar to APT1, as expected, but features a shape of the active site that precludes binding of long-chain substrates. Biochemical data demonstrate that LYPLAL1 exhibits neither phospholipase nor triacylglycerol lipase activity, but rather accepts short-chain substrates. Furthermore, extensive screening efforts using chemical array technique revealed a first small molecule inhibitor of LYPLAL1.